L-functions and Automorphic Forms: LAF, Heidelberg, February 22-26, 2016 - Bruinier, Jan Hendrik; Kohnen, Winfried (Springer, 2017)
1. P. Anamby and S. Das: Sturm-like bound for square-free Fourier coefficients -- 2. N. Andersen, K. Bringmann and K. Rolen: Images of Maass-Poincaré series in the lower half-plane -- 3. S. Börcherer: On denominators of values of certain L-functions when twisted by characters -- 4. H. Darmon, A. Lauder, V. Rotger: First order p-adic deformations of weight one newforms -- 5. S. Ehlen, N-P. Skoruppa: Computing invariants of the Weil representation -- 6. W-T. Gan: The metaplectic tensor product as an instance of Langlands functoriality -- 7. M. Grados and A. von Pippich: On scattering constants of congruence subgroups -- 8. B. Kane and S.H. Man: The Bruinier-Funke pairing and the orthogonal complement of unary theta functions -- 9. W. Kohnen and J. Sengupta: Bounds for Fourier-Jacobi coefficients of Siegel cusp forms of degree two -- 10. Y. Li: Harmonic Eisenstein series of weight one -- 11. A. Pitale, S. Abhishek and R. Schmidt: A note on the growth of nearly holomorphic vector-valued Siegel modular forms -- 12. A. Raghuram and G. Sachdeva: Critical values of L-functions for GL3 x GL1 over a totally real field -- 13. M. Raum: Indecomposable Harish-Chandara modules for Jacobi groups -- 14. M. Rösner and R. Weissauer: Multiplicity one for certain paramodular forms of genus two -- 15. H.C. Siu and K. Soundararajan: Restrictions of Hecke eigenforms to horocycles -- 16. M. Woodbury: On the triple product formula: Real local calculations -- 17. C. Alfes-Neumann: An introduction to the theory of harmonic Maass forms -- 18. S. Börcherer: Elementary Introduction to p-adic Siegel Modular Forms -- 19. E. Hofmann: Liftings and Borcherds products
Keywords: Konferenzschrift